Pendayagunaan Sumber Belajar Dalam Implementasi Strategi Penyampaian Pembelajaran Tematik - Agus Wedi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
This study aims to describe the utilization of learning resources in the implementation of thematic learning delivery strategies in the early grades of elementary school. This study used a phenomenological qualitative approach with a case study design. The results showed that there were various learning resources that were used, the occurrence of patterns of student interaction with the sources, and the structure of classical, group and individual learning forms. Utilization of these resources is influenced by internal and external factors.